2019
DOI: 10.1021/acs.energyfuels.8b04325
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Petroporphyrin Identification in Crude Oils Using Highly Selective Electron Transfer Reactions in MALDI-FTICR-MS

Abstract: Petroprophyrins are biomarkers used to extract information about petroleum genesis among other characteristics. Identification of particular types, such as Ni, Cu, Mn, vanadyl (VO), and oxygenated or sulfur-containing porphyrins, typically involves exhaustive isolation and purification processes followed by high-resolution mass spectrometry analysis using atmospheric pressure photoionization [APPI-(+)] or electrospray [ESI-(+)] sources. Simultaneous identification of all porphyrins present in a particular crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 39 publications
1
57
0
Order By: Relevance
“…Sulfur has a completely different behavior compared to that of V and Ni showing that sulfur is not mainly driving the aggregation/sequestration of V and Ni.Regarding Ni and V, similar behavior is obtained except for their LMW extracts, for which the Ni compounds consistently have a lower percentage than the V compounds. This can explain why, in most molecular MS studies,33 V petroporphyrins have primarily been identified because the Ni and V compounds in nanoaggregates associated with the HMW fraction are more difficult to ionize. 39 CONCLUSIONS The use of liquid-solid extraction as an adequate methodology for the separation of the V, Ni and S compounds present in asphaltenes based on their molecular weights is reported for the first time.…”
mentioning
confidence: 99%
“…Sulfur has a completely different behavior compared to that of V and Ni showing that sulfur is not mainly driving the aggregation/sequestration of V and Ni.Regarding Ni and V, similar behavior is obtained except for their LMW extracts, for which the Ni compounds consistently have a lower percentage than the V compounds. This can explain why, in most molecular MS studies,33 V petroporphyrins have primarily been identified because the Ni and V compounds in nanoaggregates associated with the HMW fraction are more difficult to ionize. 39 CONCLUSIONS The use of liquid-solid extraction as an adequate methodology for the separation of the V, Ni and S compounds present in asphaltenes based on their molecular weights is reported for the first time.…”
mentioning
confidence: 99%
“…65 Notably, the authors documented the separation of three distinct fractions of vanadium and nickel compounds in maltenes based on molecular weight and aggregation tendency determined using GPC. 13 The same authors performed a similar study by directly applying the technique to asphaltene using successive extraction with dimethylformamide, acetone and finally acetonitrile. Again, two highly aggregated enriched porphyrin fractions were hypothesized in the DMF and acetone fractions based on GPC.…”
Section: ■ Methods For the Extraction And Purification Of Metalloporphyrinsmentioning
confidence: 99%
“…17 Molecular transformations yield a range of structurally diverse porphyrin families that correspond to N4VO, N4VO2, N4VO3, N4VOS, and N4Ni, depending on the peripheral functional groups, as shown in Figure 1 (bottom row). 13,16 Figure 1. Geochemical transformations of chlorophylls.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Porphyrins, chelated with nickel and vanadyl, are widely described in the literature [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%